East Asia Summit or ASEAN Plus Eight – an insight into Asian regionalism from perspective of Japan - Bobowski, Sebastian (Economics of the 21st Century, 2016)
The article discusses the project of East Asia Summit – EAS, a manifestation of Asian diplomatic regionalism, launched in 2005 as a political forum of countries located in the region of East Asia, consistently evolving toward an Asia-Pacific platform of dialogue due to formal membership of Russia and the United States since 2011. A year before there was a discussion about the possibility of the constitution of the ASEAN Plus Eight formula. The author attempts to study the genesis of the EAS project, indicating an issue of membership in the regional diplomatic framework, while addressing Japan’s optics
Ekonomia XXI Wieku = Economics of the 21st Century, 2016, Nr 1 (9), s. 40-52
Keywords: East Asia Summit; ASEAN Plus Eight; Asian diplomatic regionalism; Japan; Szczyt Azji Wschodniej; ASEAN Plus Osiem; azjatycki regionalizm dyplomatyczny; Japonia